2022
DOI: 10.3389/fgene.2021.757632
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain With Persistent Radiculopathy; the Clinical Role of Genetic Variants in the Genes SOX5, CCDC26/GSDMC and DCC

Abstract: In a recently published genome-wide association study (GWAS) chronic back pain was associated with three loci; SOX5, CCDC26/GSDMC and DCC. This GWAS was based on a heterogeneous sample of back pain disorders, and it is unknown whether these loci are of clinical relevance for low back pain (LBP) with persistent radiculopathy. Thus, we examine if LBP with radiculopathy 12 months after an acute episode of LBP with radiculopathy is associated with the selected single nucleotide polymorphisms (SNPs); SOX5 rs3461655… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[ 5 , 6 , 7 ] Recently, the genome‐wide association studies (GWAS) have identified accumulated genetic loci. [ 8 , 9 , 10 , 11 ] A large‐scale GWAS study of over 500 000 individuals identified a common underlying genetic component between disc pathology and low back pain, identifying three BP‐associated loci. [ 8 ] Another large‐scale genome‐wide association study meta‐analysis identified 41 variants at 33 motifs associated with back pain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 , 7 ] Recently, the genome‐wide association studies (GWAS) have identified accumulated genetic loci. [ 8 , 9 , 10 , 11 ] A large‐scale GWAS study of over 500 000 individuals identified a common underlying genetic component between disc pathology and low back pain, identifying three BP‐associated loci. [ 8 ] Another large‐scale genome‐wide association study meta‐analysis identified 41 variants at 33 motifs associated with back pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three above mentioned loci, a follow up study by Freidin et al also found that mutations in SPOCK2 and CHST3 potentially contribute to disc generation and general back pain in a study of 509,000 European individuals ( Freidin et al, 2019 ). However, there is debate as to whether the SOX5 , CCDC26/GSDMC , and DCC loci are associated with back pain based on another study of Caucasian individuals in Norway ( Lie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%